2018
DOI: 10.1016/j.bbrep.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-derived exosomes induce putative altered pathways in biosynthesis and ion regulatory channels in glioblastoma cells

Abstract: Hypoxia, a hallmark characteristic of glioblastoma (GBM) induces changes in the transcriptome and the proteome of tumor cells. We discovered that hypoxic stress produces significant qualitative and quantitative changes in the protein content of secreted exosomes from GBM cells. Among the proteins found to be selectively elevated in hypoxic exosomes were protein-lysine 6-oxidase (LOX), thrombospondin-1 (TSP1), vascular derived endothelial factor (VEGF) and a disintegrin and metalloproteinase with thrombospondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 74 publications
(96 reference statements)
2
75
0
Order By: Relevance
“…Endothelial progenitor cells also exhibited elevated expression of angiogenic‐related factors after exposure to hypoxic exosomes. All these findings suggested that GBM cells respond to hypoxia stress through changing the transcriptome and proteome of their exosomes, and mediate their angiogenesis, progression, and treatment resistance mechanisms …”
Section: Exosomes In Hypoxia Conditionsmentioning
confidence: 94%
“…Endothelial progenitor cells also exhibited elevated expression of angiogenic‐related factors after exposure to hypoxic exosomes. All these findings suggested that GBM cells respond to hypoxia stress through changing the transcriptome and proteome of their exosomes, and mediate their angiogenesis, progression, and treatment resistance mechanisms …”
Section: Exosomes In Hypoxia Conditionsmentioning
confidence: 94%
“…EV Isolation Human breast cancer cells (MCF10A, T47D, MCF7, SUM159, MDA-MB-231, 231-LM, 231-BoM and LRCP17) were grown to approximately 80% confluency in normal growth media. Culture media were replaced with serum-free media, and cells were incubated under hypoxic culture conditions (37 • C, 1% CO 2 ) for 48 h to enhance EV production and packaging [46,47]. Culture media were harvested, and EVs were isolated as previously described [48].…”
Section: Isolation and Characterization Of Breast Cancer-derived Extrmentioning
confidence: 99%
“…A study of MSC-EVs observed increased proliferation, migration, and tube formation with hypoxia-derived EVs (1% O 2 for 72 h) as compared to those from normoxic conditions (Bian et al, 2014). Another study on glioma cells observed significantly increased tube formation by endothelial progenitor cells when treated with hypoxia (<0.5% O 2 for undisclosed time) versus normoxiaderived EVs; however, the treatments equally protected glioma cells from oxidative stress (Kore et al, 2018). Similarly, human cardiosphere-derived EVs isolated under 18 and 1% O 2 showed increased tube formation as compared to PBS control.…”
Section: Discussionmentioning
confidence: 99%